Epidemiology of Whiplash-associated Disorders Following Traffic accidents in Iceland Analysis of data from the Landspitali University Hospital from 2010- 2021 - Kristín Rut Arnardóttir 1996- (2023)
Study design: Retrospective, epidemiological study Background: Whiplash-associated disorder (WAD) is a common injury following a car accident. The incidence rate is around 300 per 100,000 individuals per year in the Western world. Whiplash can lead to a range of symptoms, both psychological and physical, and around half of those who have sustained whiplash injuries still have some symptoms one year after the incident. There is no data available, to the authors knowledge, on the epidemiology of whiplash injuries due to traffic accidents in Iceland since the beginning of the century. Objective: Calculate the incidence of whiplash injuries resulting from traffic accidents in Iceland from 2010 to 2021 by utilizing records of individuals who visited the emergency room (ER) at Landspitali University Hospital (LUH). Methods: Data from LUH was obtained for all individuals who visited the ER from 2010 to 2021 due to traffic accidents and were registered with ICPC code (International Classification of Primary Care) “traffic accident“. Incidence of whiplash injuries was calculated for each year from 2010 to 2021 and presented per 100,000 persons for each year, as well as calculating the overall average, by using population data for the capital area. Incidence of whiplash injuries was examined for age, age groups, and sex. For each year from 2010 to 2021, the average number of whiplash injuries was assessed for each month and for each weekday to see their distribution. Results: A total of 18,934 individuals came to LUH following traffic accidents from 2010 to 2021, of which 8,539 had sustained whiplash injuries (45%). The overall incidence of whiplash injuries was 328 per 100,000. The proportion of whiplash injuries was from 33.3%-52.9% through the years. Females made the majority of those who sustained whiplash (59.1%). The peak incidence was within the age group 20-24 years old, with 795 cases per 100,000. Conclusion: The proportion of individuals who went to LUH following traffic accidents and were diagnosed with ...